2022
DOI: 10.1111/head.14425
|View full text |Cite
|
Sign up to set email alerts
|

Ahead of the pain: Where we stand after a decade of growth in United Council for Neurologic Subspecialties‐certified headache subspecialists

Abstract: Objective To characterize the geographic distribution of United States (US) headache subspecialists in 2021 compared to 2012 and analyze trends in distribution of and growth by geography. Introduction Headache disorders are the second‐highest cause of disease burden worldwide. Historically, headache disorders have been treated by primary care and emergency physicians, often suboptimally. Our 2012 study identified further disparities in geographic distribution of United Council for Neurologic Subspecialties (UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…With their updated demographics data, capturing the decade of growth of headache medicine subspecialists in the United States, Kanegi and Rosen 79 found that in 2021 there was an increase in headache medicine clinicians compared to 2012, with 692 UCNS board-certified headache medicine subspecialists in 2021 as compared with 416 in 2012. However, the authors found disparities in access, with areas of higher poverty lacking headache medicine specialists.…”
Section: Factors That May Contribute To Headache Disparitiesmentioning
confidence: 99%
“…With their updated demographics data, capturing the decade of growth of headache medicine subspecialists in the United States, Kanegi and Rosen 79 found that in 2021 there was an increase in headache medicine clinicians compared to 2012, with 692 UCNS board-certified headache medicine subspecialists in 2021 as compared with 416 in 2012. However, the authors found disparities in access, with areas of higher poverty lacking headache medicine specialists.…”
Section: Factors That May Contribute To Headache Disparitiesmentioning
confidence: 99%
“…He has also conducted research on how geography, race, and gender identity affect access to neurological care and health outcomes. He plans to continue developing clinical and basic science skills as a future clinician–scientist 4 …”
mentioning
confidence: 99%
“…He plans to continue developing clinical and basic science skills as a future clinician-scientist. 4…”
mentioning
confidence: 99%